ANALYSIS OF MEANING COMPONENTS OF TASIKMALAYA CITY TRADITIONS: HAJAT LAUT, HAJAT SASIH, AND HAJAT LEMBUR IN SEMANTIC STUDY - Mila Maulidiyah; Astri Fauziah Hindasah; Fadisha Mutia Rahma; Savadila Adinda Mynur; Aveny Septi Astriani (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
In semantic studies, each word carries a distinct meaning from other words. Analyzing the components of meaning in semantics aids in discerning the significance of words when compared to others. This is evident in the context of traditions in Tasikmalaya, where similar traditional names—hajat laut, hajat sasih, and hajat lembur—exist, yet each holds unique differences. This research aims to establish the correlation between the meanings of these traditional names in Tasikmalaya and delineate the disparities among the three. The method employed is qualitative descriptive analysis utilizing meaning component analysis techniques, focusing on identifying both similarities and differences. The findings unveil commonalities and distinctions in these traditions concerning the event's purpose, timing, traditional essence, and rituals in Tasikmalaya. Thus, delving into the meaning components in semantics enhances our understanding of the names and underlying meanings behind these three traditional practices.